OPTIMALISASI MANAJEMEN DAN PROSES HYBRID TANI-TERNAK DI KWT DAWIS41 - Putra, Ikbal Rizki; Irmawa, Erwhin; Dyaksa, Gilang Argya; Prabowo, Fajar Yulianto; Putra, Brian Teo; Fernanda, Reza Dwi; Dermawan, Muhammad Deant Adzany; Sehono, Sehono (Universitas Mataram, 2025)
The Dawis41 Women's Farmers Group (KWT) in Argorejo is a forum for women to improve the village economy through goat and muscovy duck farming activities. This group faces three priority problems: the lack of alternative electricity sources for barn lighting, the lack of an independent livestock feed management system, and the lack of processing of livestock waste into compost. The purpose of this community service activity is to increase production and the implementation of management and alternative energy in KWT Dawis41. This activity is carried out through five systematic methods that include program socialization, training, technology application, mentoring and evaluation, and program sustainability. The Appropriate Technology (TTG) implemented is one solar panel unit, one feed chopper unit, and one compost mixer unit. This program successfully resolved the problems faced by partners in the areas of production and management. The implementation of TTG has succeeded in increasing the level of community empowerment with a breakdown of 100% for the Solar Panel TTG, 58% for the Animal Feed Chopper TTG, and 45% for the Compost Mixer TTG. The training also yielded positive results, with 61% of the 23 participants responding with a good understanding of TTG use and waste management. The community partnership program successfully resolved partner issues through effective TTG implementation, improving business efficiency and group empowerment.